Violence in dating: An update for adolescence - Valdivia Peralta, Maruzzella Paola (2014)
This literature review updates evidence about intimate partner violence in dating relationships, revealing a particular phenomenon, emphasizing issues such as the prevalence for both sexes, which according to various reviewed studies may range from 0.8% for sexual violence to 98% for psychological aggression. Factors associated with abuse or early sexual initiation, temporal extent of the relationship, role of parents and peers, among others; and the consequences as dropouts: teenage pregnancy, eating disorders, victimization and expression of anger primarily in men, etc. are anayzed. This review demonstrates that this phenomenon has certain peculiarities that justify a more targeted research particularly during adolescence.